(untitled) - Lee, O-Young (Tokyo, Japan, 1982)
This book consists of the following six parts: The naked truth about interpretations of Japan; Smaller is better with six examples; The culture of reductionism as manifested in nature; Reductionism as found in people and society; reductionism today; and then expansionism and the Japan of today.
Keywords: Aesthetics, japanese